MAQASHID AL-SYARIâ€™AH (Telaah dalam dimensi Ketuhanan dan Kemanusiaan) - Rasyid, Muh. Haras (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This article titled â€œMaqashid al-Syariâ€™ah (Assessing the dimensions of Divinity and Humanity)â€. Maqashid al-Syariâ€™ah, it simply means that the purpose of Allah swt, create Syariâ€™ah that govern the lives of His creatures especially humans. One of the most important goals are for the benefit of human life in all aspects, both aspects of the spiritual and physical aspect. Allah Swt. creating Syarâ€™ah, philosophically when analyzed contains two dimension. First, the absolute dimensions or non-negotiable and must be received in faith. What Allah commanded and forbidden, must be carried out (dimensions Godhead). Second, the dimensions of which there are legal aspects relating to the real conditions of human life from time to time. These aspects require reasoning or human involvement to solve the legal problems faced by humans (human dimension).